Analisis Syarat-Syarat Arbiter Dalam Undang-Undang No 30 Tahun 1999 Dan Peraturan Basyarnas Serta Implikasinya Terhadap Pelaksanaan Tugas Arbiter - Damar Chandra Prasetyo; Natama Khofifah Wardani; Danaya Karima (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the differences in arbitrator requirements under Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution and the regulations of the National Sharia Arbitration Board (BASYARNAS), as well as their implications for the implementation of arbitral duties and the quality of arbitral awards. Law No. 30 of 1999 emphasizes formal legal qualifications, independence, and efficiency to ensure legal certainty and enforceability of arbitral decisions. In contrast, BASYARNAS introduces additional moral and religious requirements, requiring arbitrators to possess integrity and competence in Islamic law and sharia economic principles. These differences influence not only the procedural approach of arbitrators, but also the substance and orientation of arbitral reasoning. While general arbitration prioritizes contractual compliance and positive law, sharia arbitration integrates legal norms with ethical and religious considerations. The findings indicate that both frameworks operate complementarily within Indonesia’s plural legal system. Strengthening arbitrators’ legal expertise and ethical awareness is therefore essential to enhance the credibility, legitimacy, and justice of arbitration as an alternative dispute resolution mechanism.